Análise teórica e experimental da transmissão de forças na junção de aduelas pré-moldadas de pontes protendidas - Donin, Christian (2020)
There is a growing demand for bridges with prestressed precast segments, thus, the need for further study and development of this system is evident. Currently, these bridges use connections between segments by joints with shear keys, which present fairly divergent design models. The aim of this work is to develop calculation models to be used in calculating the shear force of seals with shear keys, with and without epoxy adhesive, as well as for flat joints with epoxy adhesive, which can be used in bridges composed of prestressed precast segments. Therefore, the methodology employed is initially to study the problems in joints, with emphasis on joint systems that use shear keys. Next, we define joint models with shear keys in order to test them by theoretical, computational numerical analysis, using the finite element method and an experimental program. Totally, 27 joint specimens were tested in the experimental phase. It was verified that the use of epoxy adhesive in joints with shear keys provided increases in shear force up to 55.47%. Compering the proposed model for joints with shear keys and epoxy adhesive with the experimental results, we always obtained low differences, not exceeding 8%. Considering the proposed model for joints with dry shear keys, we verified that there was a maximum difference of less than 8%, with an average of less than 5%. Finally, regarding the flat joints and epoxy adhesive model, it presented a behavior very close to the experimental one, resulting in variations of less than 5%. These results and conclusions attest to the efficiency and consistency of the proposed models when compared to the theoretical models tested.